Ecommerce System for Jvirgoo_ Online Store - Chin, Hui Yi; Mohamad, Radiah (Applied Information Technology And Computer Science, 2023)
Jvirgoo_ is an online store which operates on Instagram from December 2019. There are several problems that sellers face when conducting business using existing procedures. The problems are the direct messages disappear due to the crash of Instagram, weak documentation and time wasting. The objectives in this project are to study and design an e-commerce system based on object-oriented approach, to develop an e-commerce system with web based and to evaluate the developed e-commerce system. The prototype model is used in this project. This system is expected to store the records of customers, products, orders and suppliers and the customers can place their order through this e-commerce system. Therefore, this system can be used to increase productivity and efficiency in a manageable way and benefit those sellers who do not have any e-commerce website in the future.